OPTIMISASI PEMBAGIAN TUGAS KARYAWAN MENGGUNAKAN METODE HUNGARIAN - Marline Paendong; Jantje D. Prang (JURNAL ILMIAH SAINS, 2011)
Hal penting yang perlu dipertimbangkan dalam penugasan karyawan pada â€œLia Fashion Komo Luarâ€ adalah bagaimana kondisi penugasan agar kelebihan biaya produksi minimum sedangkan pada â€œMan Taylorâ€ adalah bagaimana kondisi penugasan agar waktu produksi minimum. Dengan menggunakan metode Hungarian diperoleh hasil sebagai berikut: penugasan karyawan pada â€œLia Fashion Komo Luarâ€ agar kelebihan biaya produksi minimum adalah karyawan A ditugaskan menjahit seragam pramuka putri, karyawan B ditugaskan menjahit seragam SMA putri, dan karyawan C menjahit baju pegawai sedangkan pada â€œMan Taylorâ€ agar waktu produksi minimum adalah karyawan A ditugaskan menjahit baju kebaya, karyawan C ditugaskan menjahit rok kebaya, karyawan D ditugaskan menjahit celana panjang, karyawan E ditugaskan menjahit rok pendek, karyawan F ditugaskan mejahit pakaian dinas harian (PDH), dan karyawan G ditugaskan menjahit baju kemeja.Â OPTIMIZATION OF DISTRIBUTION WORKER ASSIGNMENTUSING HUNGARIAN METHODABSTRACTThe Important point to be observe the worker assignment on â€œLia Fashion Komo Luarâ€ is how to condition of the assignment for minimum production cost advantages. While in â€œMan Taylorâ€ is how the condition of the assignment for minimum production time. To simplify the assignment of these worker, there is a operation research method is the Assignment Problem using the Hungarian method. Assignment Problem is one case in the business world relating to the optimal assignment in which the number of worker equal to number of tasks to be done. Hungarian method is one technique for solving assignment problem consider the observation and problem formulation analysis afterwords by modifying the assignment table to the matrix of effectiveness in order to obtain optimal conditions. The results obtained by assignment of the right worker on the â€œLia Fashion Komo Luarâ€ for a minimum production cost advantage the worker A was assigned to sew scout uniform girls, worker B was assigned to sew school uniform girls, and worker C was assigned to sew officer clothes. While in â€œMan Taylorâ€ for minimum production time the worker A was asiigned to sew kebaya clothes, worker C was assigned to sew kebaya skirt, worker D was assigned to sew trousers, worker E was assigned to sew short dress, worker F was assigned to sew PDH clothes, and worker G was assigned to sew shirt clothes.